Local ozone therapy options for lumbosacral dorsopathy - Lev G. Agasarov; Tatiana V. Konchugova; Detelina B. Kulchitskaya; Olga S. Davyan; Tatiana V. Apkhanova; Anatoliy D. Fesyun; Andrey P. Rachin; Maxim Yu. Yakovlev; Kirill V. Terentev; Natalia P. Sanina (European Journal of Translational Myology, 2022)
The characteristic resistance of dorsopathies to conventional therapy explains the attention to new technologies that combine several therapeutic links and, in particular, ozone therapy. The study involved 90 patients under the age of 55 in the exacerbation phase of lumbar and sacrum dorsopathy with the leading vascular component. The patients were divided into three groups, in which basic medical and physical treatment was given. At the same time, ozone therapy was used the first two groups: the 1st group received standard ozone therapy, with a predominant selection of algic zones, the 2nd - according to the rules of biopuncture, affecting the complex of segmental, distant and "vascular" points. In the 3rd control group, the correction was limited to a standard therapeutic complex. The verification of the observed changes was carried out through clinical, psychological and electrophysiological analysis. As a result, both ozone therapy schemes (effective in 69% and 73% of observations respectively) were found to have a reliable advantage over the base complex, where 49% of patients demonstrated improvement. Differences within the ozone therapy groups themselves related to the achievement of a stable effect (in the 2nd group 2.6 days earlier) and the degree of reduction of vaso-reflex reactions (observed in 50% and 75% of observations respectively). Thus, by bringing in additional control methods, it has been proven that the implementation of ozone therapy in compliance with the rules of biopuncture ensures faster and more sustainable effects.